Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/cup.13436
|View full text |Cite
|
Sign up to set email alerts
|

Sweet syndrome with pseudocarcinomatous hyperplasia: A case report and review of the literature

Abstract: Pseudocarcinomatous (pseudoepitheliomatous) hyperplasia represents reactive epidermal change mimicking squamous cell carcinoma (SCC), owing to a variety of inflammatory and neoplastic phenomena, including deep fungal infections, CD30‐positive lymphomas, and others. We report a case of Sweet syndrome (SS) arising in a patient with acute myelogenous leukemia, with persistent orolabial involvement which mimicked SCC both clinically and microscopically, but resolved entirely with adequate corticosteroid treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
2
0
1
Order By: Relevance
“…Grunwald et al reported two types of PCH in the skin: an epithelial response with proliferation of basaloid cells and an epithelial response with proliferation of squamous cells toward cornification (4). In the present case, the histopathological findings of the nasal lesion suggested an epithelial response with proliferation of squamous cells toward cornifi- (2,12,13). Although Sweet syndrome is often seen in cases of hematologic malignancies, such as AML, PCH is a very rare dermal histopathological finding in AML (2,12).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Grunwald et al reported two types of PCH in the skin: an epithelial response with proliferation of basaloid cells and an epithelial response with proliferation of squamous cells toward cornification (4). In the present case, the histopathological findings of the nasal lesion suggested an epithelial response with proliferation of squamous cells toward cornifi- (2,12,13). Although Sweet syndrome is often seen in cases of hematologic malignancies, such as AML, PCH is a very rare dermal histopathological finding in AML (2,12).…”
Section: Discussionmentioning
confidence: 44%
“…Pseudocarcinomatous hyperplasia (PCH), also known as pseudoepitheliomatous hyperplasia, is a reactive epithelial proliferation that occurs in inflammatory conditions and malignant diseases such as CD30-positive lymphoproliferative disorders, acute myeloid leukemia (AML), non-tuberculous mycobacterial infection, and irradiation (1)(2)(3)(4)(5). PCH may be misdiagnosed as well-differentiated squamous cell carcinoma or keratoacanthoma (5,6).…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 It is generally associated with infection (especially deep fungal infection), chronic inflammation, hypersensitivity reactions, and malignancy. 2 , 4 , 5 , 6 Histologically, PEH may closely resemble SCC, especially in biopsy specimens with insufficient dermis. 5 However, unlike SCC, the pathology of pSS lacks nuclear atypia, abundant or abnormal mitoses, and prominent dyskeratosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 SS with pseudoepitheliomatous hyperplasia is rare and to the best of our knowledge, SS-like ENL with PEH and ulceration has not been described before, making it a peculiar feature in our patient both clinically and histologically, and also first of its kind. 19 The Lucio phenomenon as a cause for ulceration in leprosy is well established. 2 Characteristic histological features are epidermal and dermal necrosis with fibrinoid vasculitis and lepra bacilli in the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%